Landscape professionals' perceptions on tree retention and legislation in Kuala Lumpur / Nor Hanisah Mohd Hashim and James Donald Hitchmough - Mohd Hashim, Nor Hanisah; Hitchmough, James Donald (Faculty of Architecture, Planning and Surveying, 2016)
Environmental improvement has been on the national agenda since 1976, when the Parliament of Malaysia has announced the Town and Country Planning Act 1976 (Act 172) Part VA as a tool to preserve and conserve trees. The guidelines within the Tree Preservation Order (1995) stipulated in detail the interpretation of the 1976 Act. In addition to the Town and Country Planning Act 1976 (Act 172) Part VA, issues pertaining to tree retention were also mentioned in the Street, Drainage and Building Act 1974 (Act 133) Part II. The establishment of Federal Territory Planning Act (1982): Act 267 further strengthened the status of trees as the main catalyst of environmental conservation efforts in urban areas. The commitment to improve urban conditions continued in 1995 through the 'Garden the Nation' movement by the Federal Government. This study attempts to assess landscape professionals' perceptions towards the retaining of tree and legislation pertaining street trees in Kuala Lumpur. Data collected were based on the methodological framework. The methodological framework was divided into two: the quantitative section which deals with questionnaire surveys and the qualitative section for semi-structured interview. About 60 sets of questionnaires were distributed to the target group of various background of landscape professionals. The questionnaire was divided into three parts. Part one was allocated for questions aimed at obtaining personal information from the respondents. Part two and three were consisted of items measuring the respondents' perceptions towards their understanding on governance and practice, and tree biology. The design of the questionnaire was a combination of closed and open-ended questions, questions with 'Likert-scale' responses and also thematic drawing questions. There were seven self-administered questions which were then tested against the demographic profile of the respondents such as gender, age, ethnicity, educational attainment and occupation. A semi-structured interview was conducted to further clarify and verify the findings of the questionnaire. There were disparities among the landscape professionals' in perceiving governance and retaining trees in Kuala Lumpur city. In conclusion, the knowledge on retaining tree and tree biology should be embedded in the curriculum of the education programme as to inculcate landscape professionals into a knowledgeable person.